The Science of Sacred Sounds: A Comparative Study of Yogic Pranayama and Tibetan Buddhist Chanting Techniques (Bodhi Path, 2024)
This study explores the mechanisms and effects of sound and breath in Yogic Pranayama and Tibetan Buddhist Chanting, focusing on their use in achieving well-being, spiritual awareness, and meditative depth. It compares specific techniques like Bhramari Pranayama, Ujjayi Pranayama, and various Tibetan Chanting methods, including Gyuto and Gyume Monks' Chanting, to identify shared principles and unique characteristics of these ancient practices. The findings indicate both practices effectively use sound and breath for relaxation, stress reduction, and meditation, with Yogic Pranayama regulating breath for body-mind harmony and Tibetan Chanting using resonant sounds for spiritual depth. Both demonstrate benefits like mental clarity, emotional balance, and spiritual connectedness. Concluding that sound and breath are integral to spiritual practices, the study suggests their incorporation into modern wellness and further research for their broader application. This research contributes to understanding the therapeutic and spiritual aspects of sound-based practices, bridging ancient traditions with contemporary health and spirituality.
Keywords: Sacred Sounds; Yogic Pranayama; Tibetan Buddhist Chanting; Bhramari Pranayama; Ujjayi Pranayama; Gyuto Monks' Chanting; Gyume Monks' Chanting